1996
DOI: 10.1007/bf01969720
|View full text |Cite
|
Sign up to set email alerts
|

High genetic variability despite haplodiploidy in primitive sawflies of the genusCephalcia (Hymenoptera, Pamphiliidae)

Abstract: Abstract. Hymenoptera are haplodiploid and usually display very low genetic variation. Most data concern social or parasitic Apocrita, while the little information available for the primitive phytophagous species of the suborder Symphyta is contradictory. The present study is related to seven species of the genus Cephalcia, living in coniferous forests of Northern Eurasia and sharing spruce (Picea sp. pl.) as host plant. Individuals from 22 populations belonging to Cephalcia abietis, C. alashanica, C. arvensis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 24 publications
3
15
0
Order By: Relevance
“…However, the effective population size is also influenced by the sex ratio (Crozier, 1976;Hedrick and Parker, 1997) and by the mating system (Berkelhamer, 1983;Owen, 1985), and the levels of heterozygosity have been found to be distinct among species of the same social level (Owen, 1985). Data presented here show high levels of heterozygosity in Symphyta, as found by Sheppard and Heydon (1986), Rosenmeier and Packer (1993), and Boato and Battisti (1996). These data suggest that haplodiploidy per se does not seem to be responsible for the low levels of genetic variability in Hymenoptera.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…However, the effective population size is also influenced by the sex ratio (Crozier, 1976;Hedrick and Parker, 1997) and by the mating system (Berkelhamer, 1983;Owen, 1985), and the levels of heterozygosity have been found to be distinct among species of the same social level (Owen, 1985). Data presented here show high levels of heterozygosity in Symphyta, as found by Sheppard and Heydon (1986), Rosenmeier and Packer (1993), and Boato and Battisti (1996). These data suggest that haplodiploidy per se does not seem to be responsible for the low levels of genetic variability in Hymenoptera.…”
Section: Discussionsupporting
confidence: 59%
“…For the purpose of comparing these data with those previously reported in the literature, Table 4 presents an average value of the mean heterozygosity for Hymenoptera (Metcalf et al, 1975;Wagner and Briscoe, 1983;Crespi, 1991;Owen et al, 1992;Shoemaker et al, 1992; and unpublished data of our laboratory) and for Symphyta (Graur, 1985;Sheppard and Heydon, 1986;Woods and Guttman, 1987;Rosenmeier and Packer, 1993;Boato and Battisti, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Berkelhamer (1983) demonstrated that Hymenoptera were associated with low gene diversity values 0.037 (3.7%) vs. 51 diploid insects 0.135 (13.5%). On the other hand, Sheppard and Heydon (1986) demonstrated mean expected gene diversity values of 0.121 to 0.144 (12.1 to 14.4%) in sawflies and Boato and Battisti (1996) demonstrated a mean expected gene diversity value of 0.197 (19.7%) in Cephalcia populations. Though a direct comparison of mean expected gene diversity values can not be made between enzyme electrophoreses studies and PCR methods incorporating SSR, in the present study with G. ashmeadi we observed individual mean expected gene diversity values ranging from 2.9 to 14.3%, but a total genetic diversity value (Ht) of 23.1% for the field populations.…”
Section: Popmentioning
confidence: 91%
“…In general, genetic variation of Hymenoptera as measured by isozyme electrophoresis is approximately one-third of that found in diploid insects (Berkelhamer 1983;Graur 1985;Unruh et al 1986;Powell and Walton 1989;Owen 1993;Unruh and Woolley 1999), though there have been limited reports of high genetic diversity (Sheppard and Heydon 1986;Boato and Battisti 1996). Berkelhamer (1983) demonstrated that Hymenoptera were associated with low gene diversity values 0.037 (3.7%) vs. 51 diploid insects 0.135 (13.5%).…”
Section: Popmentioning
confidence: 95%